Harnessing artificial intelligence in understanding endometriosis - Patel, Dhwani K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Artificial intelligence (AI) models, such as neural networks and machine or language learning algorithms like ChatGPT, Microsoft Bing/Copilot, Deepseek AI, Google Gemini are emerging as new tools that can change the world. As technology grows, the opportunity of diagnosing, treating, and especially identifying early signs of any disease becomes wider. In the era of AI, this tool that is supported by machine learning and big data analytics is already demonstrating its potential in advancing the outcomes in healthcare.